Pengaruh Umur Semai dan Kompos Terhadap Pertumbuhan Bibit dalam Investigasi Kurma Lulu (Phoenix Dactylifera L.) Betina - Siti Masreah Bernas (Fakultas Pertanian, Universitas Syiah Kuala, 2020)
ABSTRACTIndonesia imported very high amount of date palm fruits about US 13,18 M, because of that it is necessary to develop a research about date palm nursary and investigation of female date, since this is a deciduos plant. The research used plastic pots for nursary and the age of nursary were 15 and 30 days and the addition of compost and without compot during nursary. Then 30 days old date palm was planted in a bigger pot and covered using coconut palm leaves for female investigation after 30 days planting. Seedling at the age of 15 and 30 days planted in the polybag for monitoring the growth ability of plant. Results showed the characteristics of a female crop was curly new growing root and curly first leaf, where curly root occured on 15 days old of nursary. Thus female investigation could be done at the age of 15 days and without waiting for the first leaf growing. Compost was very important on increasing roots and leaves growing of seedling at the age of seedling 30 days and which had one leaf had the ability to grow about 90%. It is needed further investigation on this female date palm can produce fruit and it will take up to 3 years for fruiting.